ANALISIS KORELASI BUDAYA KOREA POPULER TERHADAP SIKAP KEBANGSAAN MAHASISWA UNIVERSITAS NEGERI MAKASSAR - Suciawati, Heni; Kasmawati, Andi; Rifdan, Rifdan (Jurnal Tomalebbi, 2024)
Abstract: This study aims to: (1) Get an overview of popular Korean culture among students of Makassar State University, (2) Know and explain information related to the national attitude of Makassar State University students, (3) Know and explain information related to the relationship between popular Korean culture and the national attitude of Makassar State University students. The type of research used in this study is correlational research. Data collection techniques through questionnaire techniques (questionnaires). The results showed that: (1) Popular Korean culture among students of Makassar State University is in a high category (75%) or 75 students from a total of 100 respondents. (2) The nationality attitude of Makassar State University students is in a high category (81%) or 81 students out of a total of 100 respondents. (3) There is no significant relationship between popular Korean culture and nationality attitude.